ANALISIS PENGARUH KUALITAS WEBSITE SIMAK UNIVERSITAS SEPULUH NOPEMBER PAPUA - Hardiana; Emy L. Tatuhey (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This study aims to analyze user satisfaction toward the SIMAK Website of Sepuluh Nopember University of Papua version 1.1.7 using the End User Computing Satisfaction (EUCS) approach. SIMAK is a crucial platform in supporting students' academic activities, yet several issues persist in its implementation, such as an unfriendly interface, slow system response, and difficulty accessing features during crucial periods like course registration. This research involved 111 respondents including students, lecturers, staff, and system operators, using a questionnaire based on five EUCS dimensions: Content, Accuracy, Format, Ease of Use, and Timeliness. The validity test confirmed that all questionnaire items are valid, while reliability analysis showed Cronbach’s Alpha values above 0.9, indicating high internal consistency. The multiple linear regression results revealed that all independent variables significantly affect user satisfaction, with an R Square of 0.999, meaning the model explains 99.9% of the variance in user satisfaction. Among all factors, Accuracy emerged as the most dominant influence. Classical assumption testing confirmed that the regression model met the requirements of normality and homoscedasticity. Based on these findings, it is recommended to enhance data accuracy, improve content presentation to be more engaging and accessible, and optimize real-time system performance to support a better user experience.